ANALYSIS OF THE DISCREPANCIES IN THE ESTIMATIONS OF POVERTY AND SOCIAL INEQUALITY IN UKRAINE - Назарова, О. Ю.; Чуприна, О. О. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2014)
The analysis of social inequality and poverty in Ukraine on the basis of the comprehensive using of the existing methodological approaches to their quantitative estimation is carried out in the work. The research of the country’s achievements in the struggle against poverty and social inequality for the period of 2000-2012's is done. The significant differences in the results of using of the different methods of poverty and social inequality studying are identified, their main causes are explained.